2008
DOI: 10.1021/nn800215j
|View full text |Cite
|
Sign up to set email alerts
|

DNA Origami Design of Dolphin-Shaped Structures with Flexible Tails

Abstract: The DNA origami method allows the folding of long, single-stranded DNA sequences into arbitrary two-dimensional structures by a set of designed oligonucleotides. The method has revealed an unexpected strength and efficiency for programmed self-assembly of molecular nanostructures and makes it possible to produce fully addressable nanostructures with wide-reaching application potential within the emerging area of nanoscience. Here we present a user-friendly software package for designing DNA origami structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
197
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(200 citation statements)
references
References 20 publications
1
197
0
2
Order By: Relevance
“…Furthermore, we have demonstrated dynamic control and programmability of the box lid. In an earlier study, we demonstrated that DNA origami structures can be designed that have tunable flexible properties 16 , and here we further show that dynamic changes can be induced by sensing external signals in the environment. The application of such a 'nanorobotic' device could be to restrict the transport of material in or out of the box in a controlled fashion.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Furthermore, we have demonstrated dynamic control and programmability of the box lid. In an earlier study, we demonstrated that DNA origami structures can be designed that have tunable flexible properties 16 , and here we further show that dynamic changes can be induced by sensing external signals in the environment. The application of such a 'nanorobotic' device could be to restrict the transport of material in or out of the box in a controlled fashion.…”
supporting
confidence: 68%
“…The software package used for the box design consists of a sequence editor and an extendable algorithm toolbox 16 . We developed a program for creating realistic 3D models, which facilitated the design of the 3D edge-to-edge staple strand crossovers.…”
Section: Methods Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of these rules has resulted in the engineering and characterization of numerous DNA 3D nanoscaffolds with different connectiviities [7][8][9][10][11][12][13][14][15][16][17][18] and the ability for some of them to promote targeted delivery by functioning as DNA nano-capsules [19][20][21] or DNA nano-carriers for other functionialities [22]. Another powerful technique called DNA "origami", developed by Paul Rothemund [23], has been extended from its original scope for designing different 2D DNA shapes [24] and functional templates [25][26][27][28] Abstract Nucleic acids have emerged as an extremely promising platform for nanotechnological applications because of their unique biochemical properties and functions. RNA, in particular, is characterized by relatively high thermal stability, diverse structural flexibility, and its capacity to perform a variety of functions in nature.…”
mentioning
confidence: 99%